2019
DOI: 10.1145/3371088
|View full text |Cite
|
Sign up to set email alerts
|

Virtual timeline: a formal abstraction for verifying preemptive schedulers with temporal isolation

Abstract: The reliability and security of safety-critical real-time systems are of utmost importance because the failure of these systems could incur severe consequences (e.g., loss of lives or failure of a mission). Such properties require strong isolation between components and they rely on enforcement mechanisms provided by the underlying operating system (OS) kernel. In addition to spatial isolation which is commonly provided by OS kernels to various extents, it also requires temporal isolation, that is, properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The initial sequential CertiKOS kernel [Gu et al 2015] was decomposed into 37 certified layers consisting of C and assembly modules such as physical and virtual memory managers, context-switch libraries, thread and process managers, virtual machine managers, and page fault and trap handlers. Later versions of CertiKOS Gu et al , 2018Liu et al 2019] showed how to extend certified layers to support multicore and multithreaded concurrency, fine-grained locking, device drivers, and real-time scheduling; they have also been extended to verify not only the total functional correctness but also information-flow security properties Liu et al 2019].…”
Section: Certified Abstraction Layersmentioning
confidence: 99%
“…The initial sequential CertiKOS kernel [Gu et al 2015] was decomposed into 37 certified layers consisting of C and assembly modules such as physical and virtual memory managers, context-switch libraries, thread and process managers, virtual machine managers, and page fault and trap handlers. Later versions of CertiKOS Gu et al , 2018Liu et al 2019] showed how to extend certified layers to support multicore and multithreaded concurrency, fine-grained locking, device drivers, and real-time scheduling; they have also been extended to verify not only the total functional correctness but also information-flow security properties Liu et al 2019].…”
Section: Certified Abstraction Layersmentioning
confidence: 99%
“…The Yale FLINT Group aimed to develop a novel and practical programming architecture to build large-scale verified system software. The members of the group have made substantial contributions in the field of formal verification, such as presenting a new framework for certified binaries [9], verifying the concurrent OS kernel [10], abstracting preemptive schedulers [11], presenting a language for certified software [12], and verifying distributed systems [13].…”
Section: B the Yale Flint Groupmentioning
confidence: 99%
“…Flint used separation logic to verify the accuracy of memory sharing and data abstraction (Koenig and Shao 2018;Gu et al 2015). Meanwhile, virtual timeline was used to specify and reason for preemptive scheduling, and a novel compositional framework is proposed for reasoning Liu et al (2020). For distributed systems, a system called WormSpace was design and verified to supply an address space of the Write-Once Register Shin et al (2019).…”
Section: Related Workmentioning
confidence: 99%